ASXL3 De Novo Variant-Related Neurodevelopmental Disorder Presenting as Dystonic Cerebral Palsy - Švantnerová, Jana; Minár, Michal; Radová, Silvia; Kolníková, Miriam; Vlkovič, Peter; Zech, Michael (Neuropediatrics, 2022)
ASXL3 loss-of-function variants represent a well-established cause of Bainbridge–Ropers syndrome, a syndromic neurodevelopmental disorder with intellectual and motor disabilities. Although a recent large-scale genomics-based study has suggested an association between ASXL3 variation and cerebral palsy, there have been no detailed case descriptions. We report, here, a female individual with a de novo pathogenic c.1210C > T, p.Gln404* nonsense variant in ASXL3, identified within the frame of an ongoing research project applying trio whole-exome sequencing to the diagnosis of dystonic cerebral palsy. The patient presented with a mixture of infantile-onset limb/trunk dystonic postures and secondarily evolving distal spastic contractures, in addition to more typical features of ASXL3-related diseases such as severe feeding issues, intellectual disability, speech impairment, and facial dysmorphic abnormalities. Our case study confirms a role for ASXL3 pathogenic variants in the etiology of cerebral-palsy phenotypes and indicates that dystonic features can be part of the clinical spectrum in Bainbridge–Ropers syndrome. ASXL3 should be added to target-gene lists used for molecular evaluation of cerebral palsy.
Keywords: neurodevelopmental disorder; cerebral palsy; genetics; movement; disorder